(untitled) (Comprehensive Journal of Science, 2026)
This paper analyzes the role of renewable energy, the green economy, and the blue economy in supporting the transition to a sustainable economic model. Using descriptive and comparative approaches, the study highlights international best practices and evaluates the potential of developing countries, particularly Libya. The findings show that investing in renewable energy and adopting green and blue economy frameworks reduces pollution, diversifies the economy, and improves living standards.